Intra-atrial ECG recording: a new and safe method for implantation of Broviac catheters in children - Zachariou, Zacharias; Daum, Roland (Pediatric surgery international, 1994)
Radiologic confirmation of central venous catheter (CVC) position is mandatory due to possible complications associated with false positioning. During the last 1.5 years, we used intra-atrial electrocardiogram (ECG) recording for intraoperative placement and documentation of CVCs, in 77 cases. We recorded the extremity and intra-atrial ECGs and then performed an intraoperative X-ray, comparing the results. Intra-atrial ECG recording is a new, inexpensive, quick, and safe method for surgical positioning and documentation of Broviac catheters in children.
Gesehen am 09.09.2024